PEMANFAATAN LAHAN TANAMAN STRAWBERRY DI RT. 01 DAN RT.04 AMBARAWANG DARAT, KABUPATEN KUTAI KARTANEGARA, KALIMANTAN TIMUR - Yanzil Azizil Yudaruddin; Ranita Ramadhani; Dika Karlinda Sari; Juwari Juwari; Rizqa Nurul Surayya (Jurnal Abdi Masyarakat Ilmu Ekonomi (JAMIE), 2021)
This community service activity aims to demonstrate to the community how yards can be used for strawberry cultivation. Ambarawang Darat is a community service project in Kutai Kartanegara Regency, East Kalimantan. Due to the environmental conditions of Ambarawang Darat District which support the growth of strawberry plants, the Bugi District was chosen as the location for community service. The climate in Ambarawang Darat Village, which is at an altitude of more than 1,000 meters above sea level, is relatively cool. Here's what you need to grow strawberry plants. This community service is carried out in several stages, including the pilot demonstration plot stage, the preparation stage, and the site survey stage. Strawberry plants grow and produce optimally and show success in cultivating strawberry plants to harvest, indicating that the implementation of community service activities is going well. Cultivating strawberries in the yard is economically and environmentally profitable, and the service location is suitable for strawberry cultivation.